Is it possible to engage adolescents in community-based non-communicable disease programs?: A case study in a rural area in Yogyakarta - Fitriana Mahardani Kusumaningrum; Cati Martiyana; Luqman Afifudin; Dita Anugrah Pratiwi; Ida Susanti; Fahmi Baiquni (Journal of Community Empowerment for Health, 2021)
Adolescents are a potential segment of society to be involved in health programs. However, adolescent involvement in community-based health programs is limited, especially for non-communicable diseases. This study explores adolescents’ participation in community-based non-communicable disease programs in a rural area of Indonesia, and factors that enable or hinder their engagement. This was a qualitative case study using the data of the Hypertension Responsive Village Movement (HRVM) Program, a community empowerment program for hypertension control in Sleman Regency, Yogyakarta. Participants consisted of adolescents aged 12 to 25 years old who are involved in HRVM. The data analyzed consisted of attendance lists and meeting/activity minutes of 6 adolescents’ programs, transcripts of interviews with 2 community leaders (village head and youth organization leader), resume of a group discussion with adolescents’ representatives, video records of adolescent programs activities and field notes. Thematic data analysis was conducted to describe adolescents’ participation, as well as the barriers and enabling factors. Descriptive analysis of attendance lists and meeting/activity minutes was developed to describe the retention rate of adolescents in the program. Adolescents’ form of participation ranged from being an acceptor to initiator. In the beginning of the program, 20 adolescents participated. However, by the end of the program, only 8 (40%) adolescents remained. Enabling factors for engagement were the community leaders’ supports, the adjustment of program strategies and deliveries with adolescence needs and the availability of social capital in the form of youth organizations. The barriers were adolescents’ limited time and limited adolescents’ participation in youth organization. In conclusion, engaging adolescents in community-based programs is possible even though it provides some challenges because of the limited time adolescents spend in their community. Strengthening stakeholders’ support, adjusting program strategies and deliveries with target characteristics and utilizing social capital are important to engage adolescents in community-based programs.